Tingginya Prevalensi Angka Hipertensi dan Asam Urat di Dusun - Khairunnisa, Adella Radya; Adhitama, Anrafi Rahman; Febryansyah, Amin; Yan Putri, Aurellia Salma; Amanda, Febby Dita; Romero, Muhammad Akhtar; Anisa, Nur; Pratista, Rafi Hadrian; Yolandina, Resti; Akbar, Syirazi Kurnia; Susyanto, M. Bambang Edi (Universitas Muhammadiyah Yogyakarta, 2025)
The shift in disease patterns from infectious diseases to non-communicable diseases (NCDs) is one of the challenges faced in health development today. NCDs have become a global health threat that has been continuously increasing over the past few decades. Conditions such as diabetes mellitus (DM), hypertension, high cholesterol, and uric acid disorders no longer affect only the elderly population but are also becoming more common among younger age groups due to changes in people's lifestyles. Randusongo Hamlet is located in Donokerto Village, Turi District, Sleman Regency, Special Region of Yogyakarta, Indonesia. Donokerto Village consists of sixteen hamlets, one of which is Randusongo Hamlet. Based on field observations, the health conditions in this hamlet are relatively good, as evidenced by activities such as healthy exercise programs and the formation of health cadre groups consisting of women from the Family Welfare Empowerment (PKK) community organization. Several aspects need attention in relation to NCDs and PHBS (Clean and Healthy Living Behavior). The non-communicable diseases in this case include hypertension, diabetes, and others. Meanwhile, PHBS is related to the ten programs from the Ministry of Health, such as physical activity, smoking cessation, clean water access, nutritious food consumption, and more. This report was created using the cross-sectional method, which involves observing variables at a single point in time without implementing any specific interventions. The community empowerment activities we conducted in Randusongo Hamlet primarily focused on existing health issues. Broadly speaking, the activities centered on three main aspects that have been identified as key issues in the hamlet: obesity, NCDs, and environmental health. Our community empowerment initiatives included health education to improve the knowledge of Randusongo residents, along with its implementation through health check-ups and self-examinations for NCD prevention. Additionally, we supported volleyball activities in the hamlet to help prevent obesity and established a waste donation program to promote environmental health.